Applicability of composite materials for space radiation shielding of spacecraft. (November 2021) - Naito, Masayuki; Kitamura, Hisashi; Koike, Masamune; Kusano, Hiroki; Kusumoto, Tamon; Uchihori, Yukio; Endo, Toshiaki; Hagiwara, Yusuke; Kiyono, Naoki; Kodama, Hiroaki; Matsuo, Shinobu; Mikoshiba, Ryo; et al.
Abstract: Energetic ion beam experiments with major space radiation elements, 1 H, 4 He, 16 O, 28 Si and 56 Fe, have been conducted to investigate the radiation shielding properties of composite materials. These materials are expected to be used for parts and fixtures of space vehicles due to both their mechanical strength and their space radiation shielding capabilities. Low Z materials containing hydrogen are effective for shielding protons and heavy ions due to their high stopping power and large fragmentation cross section per unit mass. The stopping power of the composite materials used in this work is intermediate between that of aluminum and polyethylene, which are typical structural and shielding materials used in space. The total charge-changing cross sections per unit mass, σ UM, of the composite materials are 1.3–1.8 times larger than that of aluminum. By replacing conventional aluminum used for spacecraft with commercially available composite (carbon fiber / polyether ether ketone), it is expected that the shielding effect is increased by ∼17%. The utilization of composite materials will help mitigate the space radiation hazard on future deep space missions.